Synthesis of Copper Oxide (CuO) Nanoparticles and Surveying Its Bactericidal Properties against Aeromonas Hydrophila Bacteria - SF Shaffiey; M Ahmadi; SR Shaffiey; M Shapoori; H Varshoie; F Azari (Fasa University of Medical Sciences, 2015)
Background & Objective: CuO is one of the most important transition metal oxides due to its exclusive properties. It is used in various technological applications such as superconductors and gas sensors. Recently, it has been used as an antimicrobial agent against various bacterial species. In this study, we synthesized CuO nanoparticles and evaluated their antibacterial property.    Materials & Methods: Single crystalline nanoparticles of copper oxide having almost uniform particle size of 5-6 nm have been synthesized. The used technique is free from toxic solvents and amines, and it is based on a simple reaction of copper sulfate and De-ionized water (DI). In addition, their bactericidal effects against Aeromonas hydrophila ATCC 7966T bacteria were investigated. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined with well diffusion method and liquid culture for all of the Aeromonas hydrophila culture Medias.    Results: XRD(X Ray Diffraction) spectra confirmed the formation of single phase CuO nanoparticles. A minimum crystallite size of 5-6 nm was observed in the case of CuO nanoparticles. Transmission electron microscopy results corroborate well with XRD results. CuO nanoparticles exhibited inhibitory effects against Gram-negative bacteria.    Conclusion: The present study confirms that copper oxide nanoparticles have great ability as an antimicrobial agent against Aeromonas hydrophila.